Comparison of the efficiency of optimum stabilization systems with arbitrary and intended structures - Блохін, Л. М.; Білак, Н. В. (Proceedings of National Aviation University (archive), 2021)
Comparison of the efficiency defined by known algorithm of optimum stabilization system and stabilization system with the optimization parameters of the regulator in casual circumstances is examined. The graphic dependencies of estimations of efficiency systems from parameters, which are important for doing synthesis sums, are constructed.